Aceh enclave garden design - Yusof, Zeenat Begam; Noor Ariffin, Muhammad Aiman Farahi (Kulliyah of Architecture & Environmental Design, International Islamic University Malaysia, 2020)
This project aims to design a recreational park which is located at the Cultural and Malay Heritage Living Laboratory in International Islamic University Malaysia (IIUM), Gombak, in front of Kulliyyah of Architecture and Environmental Design (KAED). The park is to be designed according to Aceh Architecture as Aceh people were one of the first settlers at Gombak area. The park is divided into four plots. Each plot consists of different activities and gazebos. The gazebos were designed based on the spaces in the Aceh traditional house concept. Each gazebo is designed to respond to nature and the activities at the plot. Materials and carvings resembling Aceh architecture are to be part of the gazebo design.